Diagnostics of testicular torsion using the TWIST scale (Testicular Workup for Ischemia and Suspected Torsion) - D. E. Sablin; V. V. Sizonov; I. M. Kagantsov; P. A. Garelina; O. S. Havroha (Вестник урологии, 2023)
Introduction. Testicular torsion (TT) is the most common pediatric emergency urological pathology. To reduce the duration of the diagnostic stage, systems for assessing the risks of testicular torsion based on anamnesis and clinical symptoms were proposed. In 2013, Barbosa et al. proposed the TWIST system (testicular examination for ischemia and suspected torsion), which became the most well-known and widespread. This system makes it possible to identify groups of patients who do not require scrotal ultrasound, which reduces the number of stages in the diagnosis of TT.Objective. To evaluate the experience of using and diagnostic significance of the TWIST scale based on available data in scientific publications.Materials & methods. Review and analysis of literature data on the use of the TWIST scale.Results. We conducted an analysis of 13 publications, in which the results of using TWIST with statistical analysis were published. In all articles, the final diagnosis was established according to Doppler scrotal ultrasound or intraoperatively. Analysis of publications shows that even in large foreign medical centers there is a problem of emergency scrotal ultrasound, which increases the time of testicular ischemia with ТТ. To use the TWIST scale, only history and physical examination data are needed. Any specialist can use the scale in his practise. The low probability of TT in the low-risk group makes it possible not to perform routine scrotal revision, and, consequently, material and human resources are saved.Conclusion. Literature analysis has shown that the use of the original TWIST scale proposed by J.A. Barbosa, in case of suspected testicular torsion, has sufficient diagnostic accuracy, high sensitivity and specificity of TT detection, which significantly reduces the need for ultrasound, reduces the diagnostic time before surgery, that increases testicular survival.